Determinants of Peripheral Muscle Strength and Activity in Daily Life in People With Bronchiectasis. Issue 3 (9th December 2017) - de Camargo, Anderson Alves; Boldorini, Jacqueline C; Holland, Anne E; de Castro, Rejane A Silva; Lanza, Fernanda de Cordoba; Athanazio, Rodrigo A; Rached, Samia Z; Carvalho-Pinto, Regina; Cukier, Alberto; Stelmach, Rafael; Corso, Simone Dal
Abstract: Background: Bronchiectasis is characterized by a progressive structural lung damage, recurrent infections and chronic inflammation which compromise the exertion tolerance, and may have an impact on skeletal muscle function and physical function. Objective: The purpose of this study was to compare peripheral muscle strength, exercise capacity, and physical activity in daily life between participants with bronchiectasis and controls and to investigate the determinants of the peripheral muscle strength and physical activity in daily life in bronchiectasis. Design: This study used a cross-sectional design. Methods: The participants' quadriceps femoris and biceps brachii muscle strength was measured. They performed the incremental shuttle walk test (ISWT) and cardiopulmonary exercise testing, and the number of steps/day was measured by a pedometer. Results: Participants had reduced quadriceps femoris muscle strength (mean difference to control group = 7 kg, 95% CI = 3.8–10.1 kg), biceps brachii muscle strength (2.1 kg, 95% CI = 0.7–3.4 kg), ISWT (227 m, 95% CI = 174–281 m), peak VO2 (6.4 ml/Kg/min, 95% CI = 4.0–8.7 ml/Kg/min), and number of steps/day (3, 332 steps/day, 95% CI = 1, 758–4, 890 steps/day). A lower quadriceps femoris strength is independently associated to an older age, female sex, lower body mass index (BMI), higher score on the modified Medical Research Council scale, and shorter distance on the ISWT ( R 2  = 0.449). Biceps brachii strength is independently associated with sex, BMI, and dyspnea ( R 2  = 0.447). The determinants of number of daily steps were dyspnea and distance walked in ISWT, explaining only 27.7% of its variance. Limitations: Number of steps per day was evaluated by a pedometer. Conclusions: People with bronchiectasis have reduced peripheral muscle strength, and reduced aerobic and functional capacities, and they also are less active in daily life. Modifiable variables such as BMI, dyspnea, and distance walked on the ISWT are associated with peripheral muscle strength and physical activity in daily life.